2020
DOI: 10.15376/biores.15.2.2495-2500
|View full text |Cite
|
Sign up to set email alerts
|

Strength and stiffness of 8-inch deep mixed hardwood composite timber mats

Abstract: There is a current and pressing need to develop engineering standards for timber- and other wood-based mats. In 2018 a group of mat producers and users began discussing a potential grading specification standard specific to mats. There are large gaps in the literature regarding the performance of the available raw materials as well as bolt-laminated mat systems. This work represents a novel attempt to begin to assess the mechanical properties of timber mats. Eight-inch deep mixed hardwood timbers were graded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…For comparison, the allowable design strength (Fb) of these 3-ply bamboo mats (8,090 kPa) is approximately half of that for mixed hardwood timber mats (15,990 kPa) as reported by Owens et al (2020). By similar comparison, the stiffness (MOE) of these 3-ply bamboo mats (1,920 MPa) is approximately one quarter of that for mixed hardwood timber mats (7,650 MPa) as reported (Owens et al 2020). The stiffness would increase with minimal additional cost if the discrete bamboo lamina could be more securely fastened to each other and thereby develop better composite action.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…For comparison, the allowable design strength (Fb) of these 3-ply bamboo mats (8,090 kPa) is approximately half of that for mixed hardwood timber mats (15,990 kPa) as reported by Owens et al (2020). By similar comparison, the stiffness (MOE) of these 3-ply bamboo mats (1,920 MPa) is approximately one quarter of that for mixed hardwood timber mats (7,650 MPa) as reported (Owens et al 2020). The stiffness would increase with minimal additional cost if the discrete bamboo lamina could be more securely fastened to each other and thereby develop better composite action.…”
Section: Resultsmentioning
confidence: 80%
“…Wood and timbers are likely the most recognizable materials that are used in mat construction. Past research has examined the mechanical performance of sawn hardwood timber mats (Owens et al 2020). Yang et al (2015) studied face-laminated pine lumber beams as a raw material that was intended for use in bolt-laminated mats.…”
Section: Introductionmentioning
confidence: 99%
“…As part of graduate research, Herberg (2018) reported on the bending performance of nail-laminated crane mats. Others have reported on the mechanical properties of mixed hardwood bolt-laminated 8-inch deep mats (Owens et al 2020) and mixed oak bolt laminated 8-and 12-inch deep mats (Shmulsky et al 2021). While these research findings detail varying aspects of the flexural behavior of mats or mat components, none speaks to the behavior or design properties of three-ply, mechanically fastened, hardwood mats.…”
Section: Introductionmentioning
confidence: 97%